2005
DOI: 10.1381/0960892053576712
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypocalcemia following Total Thyroidectomy after Biliopancreatic Diversion

Abstract: Patients undergoing malabsoprtive operations for bariatric surgery are prone to disturbances of bone metabolism, but this does not commonly lead to clinical symptoms. We present a morbidly obese patient who had undergone the biliopancreatic diversion of Larrad, and presented clinical symptoms of severe hypocalcemia and tetany after total thyroidectomy. Very high doses of i.v. calcium and calcitriol and 10 days of hospitalization were required to control the symptoms and correct plasma levels. The physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…To our knowledge, others have reported hypocalcemia following thyroidectomy in patients with previous biliopancreatic diversion (BPD) [3,4]. However, we do not know of any reports of a similar problem after RYGB, which is a procedure that generally bypasses less of the small intestine when compared to BPD [5].…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, others have reported hypocalcemia following thyroidectomy in patients with previous biliopancreatic diversion (BPD) [3,4]. However, we do not know of any reports of a similar problem after RYGB, which is a procedure that generally bypasses less of the small intestine when compared to BPD [5].…”
Section: Discussionmentioning
confidence: 93%
“…The malabsorption of vitamin D interferes in the absorption of calcium and stimulates hyperparathyroidism, which in the long term leads to the occurrence of osteoporosis [11,29,31,32]. In this study, calcium deficiency was observed in the diet, and in clinical practice, the above systemic damage is encountered [10,24,29,31,32].…”
Section: Discussionmentioning
confidence: 77%
“…Studies have demonstrated that patients in the postoperative period of bariatric surgery show abnormalities in bone mass, showing hypocalcemia in as many as 15% to 48% of patients [10,29,30]. Moreover, the deficient absorption of lipid-soluble vitamins (vitamins A, E, D, and K) aggravate the malabsorption of calcium [5,6,10,19,25,29,30]. The malabsorption of vitamin D interferes in the absorption of calcium and stimulates hyperparathyroidism, which in the long term leads to the occurrence of osteoporosis [11,29,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe, symptomatic hypocalcemia has emerged years after BPD, triggered by total thyroidectomy for papillary cancer [54,55].…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%